Islam Nusantara Dalam Tinjauan Tafsir Izwaji - Musthofa Musthofa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
Islam Nusantara is an order of life that has a pattern of life style of Islamic models formed through culture acculturation, between Islamic culture including the procedures of Islamic life in addition to mahdah worship, models of clothing and other attributes with culture located in the archipelago, covering various religions such as Hinduism, Buddhism, Catholicism, Protestantism, Confucianism, which are in the Indonesian region.This study is library research. Data obtained comes from the literature, books or transcripts related to this discussion. The system of approach through Islamic anthropology, namely the pattern of life of Muslims, covers their life cycle. Data analysis method is carried out through data reduction paths, data presentation and conclusions based on the Izwaji Interpretation approach, namely mixed explanations based on the Koran, Al-Hadith and the thoughts of experts relating to the topic of discussion.Islam Nusantara aims at a peaceful Islamic life culture, which is built on the basis of acculturation of Islamic culture and the culture of the archipelago on the land of Indonesia.Nusantara Islamic culture takes place through cultural internalization that occurs through social interaction between Islamic culture and Nusantara culture, in the life cycle. It includes prenatal ceremonies (tingkeban and pitonan), birth ceremonies (azan, iqomah, and aqiqoh), wedding ceremonies (prayers, greetings, and shake hands greetings), death ceremonies (accompany of the body, traditional prayer together, and haul).